Recovery of Male Siamese Fighting Fish (Betta splendens) After Overland Shipping - Karun Thongprajukaew; Saowalak Malawa; Sukanya Poolthajit; Nutt Nuntapong; Waraporn Hahor (Animals, 2025)
Ornamental fish shipped by road or rail may spend days in transit without food, leading to a reduction in somatic growth after transportation and during acclimatization. In the present study, a time-series (0, 2, 4, 6, 8, 10, and 12 days) experiment was conducted to investigate the growth recovery of male Siamese fighting fish (Betta splendens, 1.56 ± 0.02 g body weight, n = 15 per group) transported by road for two days. Biometric changes, nesting activity, skin pigmentation, digestive enzyme activity, muscle quality, and whole-body composition, were compared across all fish groups. The recovery in growth, as indicated by final body weight, increased with post-transportation time (p < 0.05), causing a significant reversal of weight loss with a proportionally stable condition factor from day 8 until the end of observation (p > 0.05). During this time period, the fish exhibited similar bubble-nest building activity to the control group that was not transported (p > 0.05). Color parameters, digestive enzyme activities, muscle quality, and whole-body composition of fish 8 days after shipping were comparable to the control fish group (p > 0.05). Our findings indicate that an 8-day recovery time is an appropriate protocol for Siamese fighting fish acclimatization following overland shipping.